Specific biomarkers of myocardial inflammation and remodeling processes as predictors of mortality in high‐risk patients undergoing percutaneous mitral valve repair (MitraClip) - Dörr, Oliver (Clin Cardiol, 2018)
BACKGROUND: Specific matrix metalloproteinases (MMP‐2, MMP‐9) and inflammatory biomarkers (hsCRP, IL‐6) were found to be consistently up‐regulated in severe mitral valve regurgitation (MR) and are associated with mortality in heart failure patients. The aim of the present study was to examine the prognostic value of biomarkers of cardiac inflammation and remodeling processes in predicting mortality in patients with MR undergoing percutaneous mitral valve repair (PMVR). HYPOTHESIS: We hypothesize that increased cardiac inflammation and extracellular matrix turnover is predictive for mortality in patients with severe mitral regurgitation undergoing MitraClip. METHODS: A total of 210 consecutive patients undergoing PMVR were included. PMVR was performed according to standard clinical practice. Venous blood samples for biomarker analyses were collected prior to and 6 months after PMVR. Physiological parameters, medication use, safety events, and all‐cause mortality were followed over 12 months. RESULTS: PMVR was performed successfully in all patients. Twelve months after PMVR there was an effective reduction in the severity of MR (P < 0.001), and an improvement in New York Heart Association class (P < 0.01) was documented. Elevated inflammatory biomarkers (AUC(hsCRP): 0.738 [IQR, 0.626–0.849], P = 0.001; AUC(IL‐6): 0.811 [IQR, 0.724–0.899], P = 0.001) and biomarkers reflecting cardiac remodeling processes (AUC(MMP‐2): 0.723 [IQR, 0.641–0.804], P = 0.001; AUC(MMP‐9): 0.618 [IQR, 0.534–0.701], P = 0.01) were predictors of adverse cardiac events and mortality in patients with congestive heart failure undergoing PMVR. CONCLUSIONS: The present study is the first to identify biomarkers reflecting inflammation (hsCRP, IL‐6) and cardiac remodeling processes (MMP‐2, MMP‐9) as predictors of mortality in high‐risk patients undergoing PMVR.